1985
DOI: 10.1159/000149638
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Polyoma Virus and Adenovirus Replication in Mouse Cells Temperature-Sensitive in DNA Synthesis

Abstract: Mouse adenovirus multiplies, apparently without impediment, in temperature-inactivated ts A1S9, ts C1 and ts 2 mouse fibroblasts. Thus, the DNA of mouse adenovirus can replicate in the absence of functional DNA topoisomerase II, a DNA-chain-elongation factor, and a protein required for traverse of the Gi/S interface, respectively, encoded in the ts A1S9, ts C1 and ts2 genetic loci. These results are compared with those obtained with polyoma virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Various experiments have indicated that most known DNA synthesis enzymes including DNA polymerases a, ,B and y, polydeoxynucleotide ligases I and II, poly(ADP-ribose) polymerase and DNA topoisomerase I (reviewed in Sheinin et al, 1983) and DNA topoisomerase H (E.Zacksenhaus, J.Sigouin and R. Sheinin, unpublished results) are unaffected in heat-inactivated ts A1S9 cells. This is in accord with the finding that polyoma viral DNA replication, which is heavily dependent on the host DNA synthesis machinery, is not restricted in temperature-inactivated ts AlS9 cells (Sheinin, 1976b;Sheinin et al, 1985).…”
Section: Introductionsupporting
confidence: 90%
“…Various experiments have indicated that most known DNA synthesis enzymes including DNA polymerases a, ,B and y, polydeoxynucleotide ligases I and II, poly(ADP-ribose) polymerase and DNA topoisomerase I (reviewed in Sheinin et al, 1983) and DNA topoisomerase H (E.Zacksenhaus, J.Sigouin and R. Sheinin, unpublished results) are unaffected in heat-inactivated ts A1S9 cells. This is in accord with the finding that polyoma viral DNA replication, which is heavily dependent on the host DNA synthesis machinery, is not restricted in temperature-inactivated ts AlS9 cells (Sheinin, 1976b;Sheinin et al, 1985).…”
Section: Introductionsupporting
confidence: 90%
“…On the other hand, DNA repair replication proceeds handily even after the ts 2 protein has undergone inactivation. Denaturation of the ts 2 protein does not directly prevent replication of the mouse adenovirus DNA (Sheinin et al, 1985a) or of the linear, double-stranded DNA form of the MoMuLV genome (Richter et al, 1984). On the other hand, synthesis of Py DNA and conversion of the first MoMuLV DNA product to its covalently closed, superhelical intermediate are dependent upon the functional integrity of the ts 2 protein.…”
Section: Discussionmentioning
confidence: 97%
“…Temperature-inactivated ts 2 cells are unable to support replication of polyoma (Py) virus DNA (Slater & Ozer, 1976;Sheinin et al, 1985a). In contrast, they do carry out synthesis of mouse adenovirus DNA (Sheinin et al, 1985a) and of linear, double-stranded Moloney murine leukemia virus (MoMuLV) DNA (Richter et al, 1984).…”
mentioning
confidence: 99%